The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1080/10538712.2011.573458
|View full text |Cite
|
Sign up to set email alerts
|

Early Marriage, Rape, Child Prostitution, and Related Factors Determining the Psychosocial Effects Severity of Child Sexual Abuse in Ethiopia

Abstract: This study was aimed at identifying factors that determine the psychosocial effects severity of child sexual abuse. Data were collected from 318 female children in Ethiopia using the Children's Impact of Traumatic Events Scale-Revised and the Rosenberg Self-Esteem Scale. The results revealed that respondents who survived rape and child prostitution were more symptomatic than those who were married early. Respondents for whom less time had elapsed since their first experience of abuse demonstrated a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Resultant negative psychosocial outcomes, such as feelings of guilt, stress, self-blame, anxiety and depression, are common and associated with sexual and HIV-related risks [12,13]. Reasons for increased risk include low self-esteem and self-efficacy, vulnerability to sexual abuse, limited educational opportunities and communication skills, and inability to negotiate safer sex [14].…”
Section: Introductionmentioning
confidence: 99%
“…Resultant negative psychosocial outcomes, such as feelings of guilt, stress, self-blame, anxiety and depression, are common and associated with sexual and HIV-related risks [12,13]. Reasons for increased risk include low self-esteem and self-efficacy, vulnerability to sexual abuse, limited educational opportunities and communication skills, and inability to negotiate safer sex [14].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome variable for this study was age at first marriage (binary) either below 18 or 18 and above. The variables that may influence early marriage include age, religion, respondents' highest education attainment, educational status of husbands/parents, occupational status of respondents, occupational status of parents, media exposure, and household wealth status, residence, and region (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Variables Of the Studymentioning
confidence: 99%
“…In Ethiopia, several studies identified that education, harmful tradition practice, income, family size, media exposure and culture of the community were the significant factors associated with early marriage (9)(10)(11)(12)(13)(14)(15)(16). So far different studies in Ethiopia done to identify the factors associated with early marriage.…”
Section: Introductionmentioning
confidence: 99%
“…13 There seems to be marriage child abuse, with clemency for ignorance and probably sexual behaviour of the girl involved in some cases. 14,15 It is important for parents' to protect the sexual virtue of their daughters, especially in a culture that forbids premarital sex. The Urhobos constitute one of the minority tribes in Nigeria, but a dominant tribe in Delta State.…”
Section: Introductionmentioning
confidence: 99%